Robustness of Macroeconomic Indicators of Capital Mobility - Mendoza, Enrique (Washington, D.C. : International Monetary Fund, 1992)
The performance of macroeconomic indicators of capital mobility is examined in the context of an intertemporal equilibrium model of a small open economy. Recursive numerical solution methods are used to compute measures of consumption smoothing, savings-investment correlation, and the variability and output-correlation of investment that characterize the model in the presence of income disturbances. None of these statistics is a reliable indicator of capital mobility unless information regarding differences in preferences, technology, and the nature of stochastic shocks can be taken into account.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet